The Impact of Digital Marketing Capabilities and Data Literacy on MSME Marketing Performance in Kubu Raya Regency with the Mediating Role of Customer Engagement in the Digital Acceleration Era - Dina Octaviani; Sigit Sugiardi; Rustam; Dini Oktarika (Fundamental and Applied Management Journal, 2026)
MSMEs in Kubu Raya Regency operate in a regional business environment where digital platforms are increasingly used to expand market reach, maintain customer relationships, and respond to changing consumer behavior. However, differences in digital marketing capability and data literacy may limit how effectively MSMEs convert digital adoption into measurable marketing performance. This study examines the effects of Digital Marketing Capability and Data Literacy on Marketing Performance, with Customer Engagement positioned as a mediating variable. A quantitative survey was conducted involving 150 MSME owners and/or managers selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that Digital Marketing Capability and Data Literacy are positively associated with Customer Engagement and Marketing Performance, while Customer Engagement is also positively related to Marketing Performance. The mediation results indicate that Customer Engagement helps explain the relationship between digital capability, data literacy, and marketing outcomes, although the strength of the mediation should be interpreted cautiously and supported by complete reporting of indirect effects, direct effects, confidence intervals, and VAF values. This study contributes to digital marketing research by highlighting Customer Engagement as a behavioral mechanism that links internal digital readiness with MSME marketing outcomes in a regional Indonesian context. Practically, the findings suggest that MSMEs should not only adopt digital tools but also strengthen data-based decision-making and customer interaction strategies to improve marketing effectiveness.